Peran Filsafat dalam Pembentukan Akhlak dan Etika Peserta Didik di MTs Negeri 5 Demak - Masithoh, Fisa Bela; Mujiburrohman, Mujiburrohman (Lembaga Yasin AlSys, 2025)
This study aims to examine the role of philosophy in shaping the morals and ethics of students at MTs Negeri 5 Demak. Within the context of Islamic education, philosophy plays a fundamental role in establishing a moral and ethical foundation that supports the development of well-guided personal character. A qualitative approach was used to explore the application of philosophical thought in classroom instruction and its impact on students’ character development. The study focuses on linking philosophical teachings with the educational practices implemented by teachers in cultivating students’ moral and ethical behavior. The findings reveal that the teaching of philosophy at MTs Negeri 5 Demak goes beyond textual theoretical understanding and is oriented toward the internalization of philosophical values in everyday life. Teachers serve as facilitators, guiding students to understand and practice ethical and moral principles from Islamic philosophy, such as wisdom, justice, and responsibility. Thus, philosophy functions as a crucial instrument in character formation, enabling students to become not only academically capable but also morally upright in both social and spiritual life. This study is expected to contribute to strengthening the integration of philosophy in Islamic education to shape an ethical and character-driven younger generation.